Makna Simbolik Lagu Boru Panggoaran Karya Tagor Tampubolon - Emmi Simangunsong; Ance Panggababean; Junita Batubara; Ronald Heriko Saragih; Elvita Purba (Departement of Mathematics Education, 2023)
This article discusses the song Boru Panggoaran by Tagor Tampubolon which was released in 2016 and popularized by Victor Hutabarat. The theories used in this study are Roland Barthes' semiotic theory for explaining the meaning of songs, Malm and Prier's theory for the study of music analysis. The song Boru Panggoaran is sung in a pop music style. This study uses a qualitative approach. The result of the research is that the Boru Panggoaran song uses two kinds of symbols, namely verbal symbols and nonverbal symbols. Verbal symbols in the form of poetry or song lyrics that contain meaning about parents' hopes for their eldest daughter who will protect and guide them later in their old age. The non-verbal symbols are in the form of beautiful and gentle song elements from a father or mother, which makes the song sound like 'persuading' their eldest daughter to willingly and sincerely look after her with great affection in her old age.